2015
DOI: 10.1073/pnas.1514761112
|View full text |Cite
|
Sign up to set email alerts
|

Neural mechanisms of social decision-making in the primate amygdala

Abstract: Social decisions require evaluation of costs and benefits to oneself and others. Long associated with emotion and vigilance, the amygdala has recently been implicated in both decision-making and social behavior. The amygdala signals reward and punishment, as well as facial expressions and the gaze of others. Amygdala damage impairs social interactions, and the social neuropeptide oxytocin (OT) influences human social decisions, in part, by altering amygdala function. Here we show in monkeys playing a modified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
120
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 134 publications
(132 citation statements)
references
References 70 publications
12
120
0
Order By: Relevance
“…It has been recently shown that in the basolateral amygdala of monkeys there are neurons that mirror value of rewards delivered to self and others (Chang et al, 2015), suggesting a possible role of such neurons in vicarious experience of emotions. However mirror mechanism is not the only possible explanation of vicarious emotions.…”
Section: Do Mirror Neurons Control Social Emotions?mentioning
confidence: 99%
“…It has been recently shown that in the basolateral amygdala of monkeys there are neurons that mirror value of rewards delivered to self and others (Chang et al, 2015), suggesting a possible role of such neurons in vicarious experience of emotions. However mirror mechanism is not the only possible explanation of vicarious emotions.…”
Section: Do Mirror Neurons Control Social Emotions?mentioning
confidence: 99%
“…Hypothalamic neurons that release the neuropeptide oxytocin respond selectively to social information, and oxytocin plays a central role in the regulation of social behaviors, such as maternal care, attachment, and social memory [55,114,124128]. Importantly, specific neural circuitry likely mediate these effects [55,127,129131]. Studies have validated the prosocial effects of oxytocin in humans [132134] and elaborated its role in more complex, human-level behaviors such as trust and empathy [135,136].…”
Section: Figurementioning
confidence: 99%
“…This sensitivity decreased proportionally with social distance between the two monkeys as measured in their home environment, and was correlated with the amount of mutual gaze and mutual eye blinking observed between partners [66]. In a similar experiment, researchers trained rhesus macaques to play a modified version of the classic dictator game while recording from single neurons in the basolateral amygdala [67]. They identified neurons that signaled the value of rewards for both self and for a social partner when dictators made overt decisions to give or withhold reward but not when the computer made the decisions, suggesting an active role for these neurons in social decision making.…”
Section: Primate Specializations In Social Behavior and Cognitionmentioning
confidence: 99%